7th International Conference on Image Formation in X-Ray Computed Tomography 2022
DOI: 10.1117/12.2646384
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the cone-beam CT field-of-view using two short scans with displaced centers of rotation

Abstract: A robotic cone-beam computed tomography (CT) scanner has inherent advantages. In particular, it enables source and detector trajectories capable of extending the field-of-view (FOV) of the reconstructed CT images, where the FOV is defined as the region in the source trajectory plane for which all ray lines are acquired (at any position and direction in this plane). Previous extensions of the FOV used an offset detector or a displaced center of rotation and a single full 360 • scan. However, due to limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This may lead to lateral truncation when scanning the chest and pelvis sites. One can achieve a large field-of -view by joining two small field-of -view images, as demonstrated by Belotti et al 36 and Karius et al 37 for circular trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to lateral truncation when scanning the chest and pelvis sites. One can achieve a large field-of -view by joining two small field-of -view images, as demonstrated by Belotti et al 36 and Karius et al 37 for circular trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Note that Niu et al and Park et al 22,23 both reference the capability of this method to correct for beam hardening, which would interfere with Joseph and Spital method. Therefore, we did not apply the bone-specific beam-hardening correction to this dataset, and only used the polynomial approach from Equation (10). Each projection dataset was recon-structed with RTK 25 and having applied Equation (10) in the projection domain, f (x) values obtained from Equation (4) are normalized so that 𝜇 water = 1 and scaled to HU by applying:…”
Section: Ff Ff212mentioning
confidence: 99%
“…Previous works suggested that multiple scans could also be combined to virtually increase the system's lateral angle 7 or achieve sufficient data for short (less than 360$^{\circ}$) scan 8 reconstruction 9 . A case study of FOV extension in a limited range of motion 10 is the robotic CBCT scanner currently in use at the CNAO (Figure 2). This scanner offers a displaced center of rotation (DCoR) geometry 11 by decoupling the robotic end‐effector (tooltip T) from the imaging isocenter I.…”
Section: Introductionmentioning
confidence: 99%